Circulating Neutrophil Extracellular Traps Are Elevated in Patients With Deep Infiltrating Endometriosis. (January 2019) - Munrós, Jordina; Tàssies, Dolors; Reverter, Joan Carles; Martin, Lidia; Pérez, Amelia; Carmona, Francisco; Martínez-Zamora, María Ángeles
Neutrophil extracellular traps (NETs) have been described to be related to the pathogenesis of inflammatory and autoimmune conditions. Endometriosis is currently considered a chronic inflammatory condition. Therefore, we performed a preliminary case–control study to compare the circulating plasma NET levels in patients with surgically confirmed endometriosis (E group, n = 82) and those of patients without surgical findings of endometriosis (C group, n = 35). Venous blood samples were obtained at the time of surgery. Circulating plasma NET levels were assessed as histone–DNA complexes (ie, nucleosomes) by a quantitative sandwich enzyme-linked immunosorbent assay. The results were expressed in arbitrary units. Circulating plasma NET levels were significantly higher in the E group compared with the C group (median [25th; 75th percentiles]): E group: 0.734 [0.484; 1.363]; C group: 0.541 [0.411; 0.653]; P = .005). The subanalysis of E group patients with deep infiltrating endometriosis (DIE group) or without DIE (non-DIE group) showed that plasma NET levels were higher in the DIE group ( P = .02). No differences were observed in NET levels among patients with and without severe pelvic pain or in patients with and without infertility, regardless of the presence of endometriotic lesions. Therefore, our study shows significantly higher NET levels in patients with endometriosis, which seem to be attributed to increased levels in the subgroup of patients with DIE, suggesting that the presence of elevated circulating plasma NET levels may reflect an inflammatory status in this gynecological condition. Further research is warranted to confirm our findings and to assess the exact role of NETs in the pathophysiological mechanisms of endometriosis.